Development of STEM-PjBL-Based E-Modules on Hydrocarbon to Improve Learning Outcomes of Grade XI High School Students - Putri E. Simamora; Susilawati Amdayani (Jurnal Akademika Kimia, 2026)
The 21st-century national education system faces complex challenges in preparing qualified, skilled human resources capable of addressing global educational challenges. Science, Technology, Engineering, and Mathematics are alternative learning solutions for this century. This study aims to conduct a needs analysis and assess the Validity, Practicality, Effectiveness, and Response of students to E-Modules based on STEM-PjBL. This study was conducted at SMAN 13 Medan, and the sample was class XI-2. The research approach is Research and Development (R&D), and the development model is 4-D (Four D). The data collection techniques are interviews, observations, questionnaires, and tests. Data analysis in the validity test uses the Cohen’s kappa formula, and the effectiveness test uses the N-Gain test. The results obtained indicate that the needs analysis shows that teachers have not maximized the use of the PjBL learning model and have never used E-Modules based on STEM-PjBL, and the books used do not contain projects or STEM. 66.7% of students reported sometimes feeling bored during the learning process because the media used or the teacher’s teaching methods are not engaging. 75% need new teaching materials to improve students’ knowledge of hydrocarbon lessons, in the form of E-Modules based on STEM-PjBL. In the feasibility test, the average Cohen’s kappa (k) for material experts was 0.81 and for media experts was 0.85. So, the average feasibility test score was 0.83, placing it in the very high category, and the e-module was declared feasible. In the teacher’s practicality test, the average Cohen’s kappa was 0.97, placing it in the very high category and deemed practical. The STEM-PjBL-based e-module achieved an N-Gain value of 0.56 in the moderate category, and the student response test obtained an average Cohen’s kappa of 0.89 in the very high category.